Low‐Voltage and Stretchable Organic Field Effect Transistor Array Based on Tri‐Layer Elastomer Dielectric for Gas Sensing - Xiaoying Zhang; Xiangxiang Li; Weiyu Wang; Hongchen Jiang; Xinran Zheng; Huiqi Yang; Xin Ye; Hui Yang (Advanced Electronic Materials, 2025)
Abstract Stretchable organic field‐effect transistors (OFETs) based gas sensors have attracted significant attention due to their inherent merits such as excellent mechanical compatibility, flexibility, and signal amplification capabilities. However, achieving low‐voltage operation remains challenging, which limits their practical application. Herein, a tri‐layer dielectric design is developed to achieve low‐voltage, high‐mobility stretchable organic transistors for gas sensors. The tri‐layer dielectric, consisting of a high‐κ polymer film, a non‐polar polymer layer, and a cross‐linking layer, allows the transistors to operate at −5 V. The stretchable transistor‐based gas sensors exhibit high sensitivity of gas detection capability. Thus, stretchable field‐effect transistors based on tri‐layer dielectrics offer a promising strategy for advancing wearable gas sensors.